2014
DOI: 10.1007/s10803-014-2245-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Play Groups: Promoting Symbolic Play and Social Engagement with Typical Peers in Children with ASD Across Settings

Abstract: Children with autism spectrum disorders (ASD) face pervasive challenges in symbolic and social play development. The Integrated Play Groups (IPG) model provides intensive guidance for children with ASD to participate with typical peers in mutually engaging experiences in natural settings. This study examined the effects of a 12-week IPG intervention on the symbolic and social play of 48 children with ASD using a repeated measures design. The findings revealed significant gains in symbolic and social play that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 52 publications
2
55
0
7
Order By: Relevance
“…Studies examining the benefits of combining two of these interventions, direct instruction and peer-mediated approaches, are reporting marked improvements in children’s communication with peer partners (Kamps et al, 2002; Kamps, Mason, Thiemann-Bourque, Feldmiller, Turcotte, & Miller, 2014; Thiemann & Goldstein, 2004; Wolfberg, DeWitt, Young, & Nguyen, 2014) and in greater nominations or playing more central roles in classroom social networks (Kasari, Rotheram-Fuller, Locke, & Gulsrud, 2011). Combining these two approaches follows recommendations of research reviews and investigations of effective social interventions that specify the need for direct instruction of specific social behaviors and a focus on the social-pragmatic use of language to interact with others (Goldstein, 2002; Kamps et al, 2002; Koegel, 2000; Reichow & Volkmar, 2010).…”
mentioning
confidence: 99%
“…Studies examining the benefits of combining two of these interventions, direct instruction and peer-mediated approaches, are reporting marked improvements in children’s communication with peer partners (Kamps et al, 2002; Kamps, Mason, Thiemann-Bourque, Feldmiller, Turcotte, & Miller, 2014; Thiemann & Goldstein, 2004; Wolfberg, DeWitt, Young, & Nguyen, 2014) and in greater nominations or playing more central roles in classroom social networks (Kasari, Rotheram-Fuller, Locke, & Gulsrud, 2011). Combining these two approaches follows recommendations of research reviews and investigations of effective social interventions that specify the need for direct instruction of specific social behaviors and a focus on the social-pragmatic use of language to interact with others (Goldstein, 2002; Kamps et al, 2002; Koegel, 2000; Reichow & Volkmar, 2010).…”
mentioning
confidence: 99%
“…Across the four cases of children with ASD and their paired classmates, our first main finding was that two children with ASD had a higher overall level of playfulness than their typically developing classmates (pairs 1 and 3). This was an unexpected finding as previous literature has consistently reported that children with ASD have lower developed skills in play and social interaction than their typically developing peers (Skaines et al ., ; Wolfberg et al ., ). One reason for this difference could have been the presence of existing friendship in the pairs anecdotally reported by their class teachers.…”
Section: Discussionmentioning
confidence: 97%
“…The results of this study provide some understanding of the play skills of children with ASD and discuss the determinants that impact these skills. Consideration needs to be made in relation to age, interests and pre‐existing friendships when selecting playmates (Wolfberg et al ., ). Similarly, Wolfberg et al . and DiSalvo and Oswald () supports these considerations when determining appropriate playmates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations